THE DYNAMICS OF INSTITUTIONAL ARRANGEMENT FOR IMPROVING EXPORT COMPETITIVENESS OF BESUKI NA-OOGST TOBACCO IN JEMBER REGENCY INDONESIA - Adhitya Wardhono; Josi Ali Arifandi; Yulia Indrawati (UNEJ e-Proceeding)
The challenge of the demand dynamic for international market standard and quality becomes logical consequences for all parties to pay a serious attention. Specific attention should be addressed not only to cultivation technique but also to the institutional management in every chain of Besuki Tobacco Na-Oogst cultivation. This research is conducted to formulate the strategy to develop the insititution amongst policy makers and farmers association of Besuki tobacco Na-Oogst in Jember Regency. The analysis method applied in this research is descriptive analysis using Analytical Hierarchy Process (AHP) to count for stakeholders’ perception related to the the development of institutional cultivation business of Besuki tobacco Na-Oogst in Jember Regency. Data are obtained by conducting in-depth interview and focus group discussion amongst all parties related including farmers, farmers’ association, exporters, exporters association, and the local government. The findings shows that the main priority factors to develop institution is the access to policy making from the government and the business players. Farmers are the most prioritized in the institution development of Besuki Tobacco Na-Oogst. The access to information and knowledge is crucial to increase productivity and to sustain the production as well as the market access. The effectiveness and the producers’ sustainability in the institutional management along with the market players and the policy makers are the result of the interrelation amongst three matters, bonding, bridging and linking. This becomes crucial in the national and international market access to generate positive sum game to collaborate, achieve and increase profit and to share benefit and loss.